1992
DOI: 10.1515/znb-1992-1118
|View full text |Cite
|
Sign up to set email alerts
|

Studies with Alkylheteroaromatic Carbonitriles: A Novel Synthesis of Pyrazolo[2′,3′: 3,4]benzo[c]-1,2,4-triazine

Abstract: A novel synthesis of derivatives of the title ring system by reacting methylpyrazolo[5,1-c]-1,2,4-triazin-6-carbonitriles (9) with sulphur and subsequent treatment of the resulting thienopyrazolotriazines with acetivated double bond system is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The latter can be cyclized either through formyl derivatives B (in the presence of water) formed through the elimination of a dimethylamine fragment or directly due to its cleavage, which leads to the formation of aromatic products C . 3,9…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The latter can be cyclized either through formyl derivatives B (in the presence of water) formed through the elimination of a dimethylamine fragment or directly due to its cleavage, which leads to the formation of aromatic products C . 3,9…”
Section: Resultsmentioning
confidence: 99%
“…Consideration of the literature data on the interaction of diazoazoles or azole diazonium salts with enamines, showed that the published discussions about the mechanisms of these interactions, as well as the conclusions drawn, are not supported by the experimental data. [3][4][5][6][7][8][9][10] We collected all the proposed pathways and main intermediates and they are shown in Scheme 2. The first of the proposed hypotheses considers the formation of azolo[5,1-c][1,2,4]triazines C as a result of a C-azo coupling reaction of the C-2 of the activated double bond of enamines with the corresponding diazonium salts to afford azo intermediates A.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations